2018
DOI: 10.1186/s12862-018-1156-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for late Pleistocene origin of Astyanax mexicanus cavefish

Abstract: BackgroundCavefish populations belonging to the Mexican tetra species Astyanax mexicanus are outstanding models to study the tempo and mode of adaptation to a radical environmental change. They are currently assigned to two main groups, the so-called “old” and “new” lineages, which would have populated several caves independently and at different times. However, we do not have yet accurate estimations of the time frames of evolution of these populations.ResultsWe reanalyzed the geographic distribution of mitoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
4
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(101 citation statements)
references
References 82 publications
4
91
4
2
Order By: Relevance
“…Recent studies revealed that cavefish lineages are much younger than previously thought, from less than 20,000 [5] to about 200,000 [6] years old, implying that the evolution of numerous cave-related phenotypes may have occurred over relatively short time periods. Furthermore, troglomorphic phenotypes are maintained in A. mexicanus cavefish despite the lack of complete isolation between surface fish and cavefish populations [6][7][8][9].…”
Section: Introductionmentioning
confidence: 92%
“…Recent studies revealed that cavefish lineages are much younger than previously thought, from less than 20,000 [5] to about 200,000 [6] years old, implying that the evolution of numerous cave-related phenotypes may have occurred over relatively short time periods. Furthermore, troglomorphic phenotypes are maintained in A. mexicanus cavefish despite the lack of complete isolation between surface fish and cavefish populations [6][7][8][9].…”
Section: Introductionmentioning
confidence: 92%
“…An alternative explanation for the retention of CPD photolyase function in cavefish may relate to the length of time that evolution has occurred in the dark cave environment. In support of this interpretation, recent microsatellite polymorphism analysis has suggested that surface and cave populations of Astyanax that may have diverged less than 20,000 years ago [61] carry no mutations in the photolyase coding sequences ( [25] and AstMex102 database in ENSEMBL vs92). In contrast, geological evidence Figure S5).…”
Section: Loss Of Photolyase Function In P Andruzziimentioning
confidence: 98%
“…Population genetics analyses performed on the Astyanax mexicanus cave and surface system have demonstrated the co-existence in the El Abra region of two mitochondrial haplotypes, A and B, initially defined after the ND2 gene sequence (Dowling et al 2002;Strecker et al 2003Strecker et al , 2004Ornelas-Garcia et al 2008). These mitochondrial DNA data have been used to propose evolving scenarii on the relatedness of Astyanax cave and surface populations in the region (Fumey et al 2018). Here, we used 16S rRNA mitochondrial sequence analysis to start documenting the genetic lineage of the newly discovered Chiquitita cavefish population.…”
Section: Discussionmentioning
confidence: 99%